INTERNALIZATION OF METAPHYSICAL VALUES IN ISLAMIC RELIGIOUS EDUCATION IN THE MODERN ERA - Mega Dini Fitriani; Mhd. Habibu Rahman; Fajar Rahman; Elsa Padia (PT. Jurnal Center Indonesia Publisher, 2026)
Islamic Religious Education (IRE) in the modern era is often trapped in an approach that is overly textual, dogmatic, and focused solely on legal aspects (fiqh) and rituals. This results in the marginalisation of the metaphysical dimensions of Islam—such as the concept of divinity (uluhiyah), the nature of humanity, the unseen world, the purpose of creation, and the spiritual relationship with Allah—which are in fact the foundation of the meaning and intrinsic motivation of all religious teachings. Without the internalisation of these metaphysical values, religious education risks becoming formalistic and unable to respond to existential challenges and spiritual crises amid the onslaught of materialism and secularisation in the modern world. This article aims to analyse the urgency and strategies for internalising metaphysical values within the framework of contemporary Islamic Religious Education, as well as to formulate an approach model relevant to the modern era. This study uses a qualitative method with a philosophical-analytical library research approach. Data were collected from primary sources such as the Qur'an, Hadith, and the works of classical and contemporary Islamic thinkers on education and metaphysics. The analysis was conducted hermeneutically and deductively to develop a conceptual framework. The analysis shows that the internalisation of metaphysical values in PAI is crucial for: (1) building a holistic Islamic worldview, (2) developing a deep spiritual awareness (ihsan), (3) providing a solid moral foundation that transcends positive law, and (4) creating mental-spiritual resilience in facing modern complexities. To achieve this, it is necessary to reorient the PAI curriculum to integrate metaphysical elements through an interdisciplinary approach (linking it to science, psychology, and philosophy), reflective and contemplative learning methods (such as tadabbur and tafakkur), and the use of digital technology as a medium for creative spiritual exploration.